2016
DOI: 10.1186/s12886-016-0305-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical trial of Intravitreal aflibercept treatment for PolypoIdal choroidal vasculopathy with hemorrhage or exudation (EPIC study): 6 month results

Abstract: BackgroundPolypoidal choroidal vasculopathy is a variant of choroidal neovascularization and neovascular age related macular degeneration presenting with hemorrhagic and exudative changes within the macula and/or peripapillary region leading to vision loss. In contrast to neovascular age related macular degeneration, polypoidal choroidal vasculopathy has differing clinical manifestations and treatment strategies. Historically, polypoidal choroidal vasculopathy complexes are less responsive to anti-vascular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…For PCV treatment, intravitreal aflibercept injection shows comparable results to PDT in terms of regression of polyps with stabilization of vision [15,16]. Hosokawa et al [15] reported that, at six months after aflibercept injection, polyp lesions were completely resolved in 77.7% of patients.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…For PCV treatment, intravitreal aflibercept injection shows comparable results to PDT in terms of regression of polyps with stabilization of vision [15,16]. Hosokawa et al [15] reported that, at six months after aflibercept injection, polyp lesions were completely resolved in 77.7% of patients.…”
Section: Introductionmentioning
confidence: 88%
“…Recent work investigating the effectiveness of aflibercept treatment in PCV has documented polyp regression rates following intravitreal administration as falling between 67% and 77.7% [15,16,21]. For this reason, aflibercept monotherapy may be considered a comparable treatment option to PDT in patients with PCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(111) Retrospective studies comparing aflibercept and ranibizumab have demonstrated similar significant improvements in vision and decreased central foveal thickness for both treatments. (113,115,117,121) However, aflibercept treated eyes had more frequent polyp regression (34–75%) than ranibizumab treated eyes (22%). (113,115,117,121) Additionally, retrospective studies of ranibizumab “non-responders” who were switched to aflibercept treatment demonstrated reduced exudation, reduced choroidal thickness, and stable or improved vision.…”
Section: Management Of Pcvmentioning
confidence: 99%
“…The detection of PCV is important; although eyes with PCV often have good visual outcomes with intravitreal anti-vascular endothelial growth factor (VEGF) injection monotherapy, eyes with PCV are more likely to be resistant to monotherapy than eyes with other subtypes of exudative AMD [6][7][8][9]. Once PCV is diagnosed, combination therapy with photodynamic therapy (PDT) and intravitreal anti-VEGF injections may have a higher chance of improving vision and promoting regression of polyps, DOI: 10.1159/000481540 edema, and subretinal fluid while decreasing the number of intravitreal injections needed and overall treatment burden for these patients [10,11].…”
Section: Introductionmentioning
confidence: 99%